(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluating the treatment results and adverse effects of some traditional medicine interventions on patients with cervical spondylosis at Thai Binh provincial Traditional Medicine Hospital. Method: A controlled intervention study with pre-post evaluation involving 60 patients (30 research groups, 30 control group) who were predicted to have cervical spondylosis. Results: The proportion of research groups subjects with good treatment results was 66.7%, and fair was 33.3% (different from the control group, p < 0.05). The symptoms, according to traditional medicine, decreased statistically significantly between before and after treatment; however, no difference was found between the research groups and the control group. There was a small number of patients in the research groups and the control group who had blood when the needle was removed. The survival rates of the patients were stable after treatment. Other undesirable effects were detected during the treatment. Conclusion: The method of electroacupuncture and acupressure massage combined with paraffin in the treatment of cervical shoulder arm syndrome caused by cervical spondylosis has the effect of pain relief and rehabilitation of cervical spine motor function.